2013
DOI: 10.5964/ejcop.v2i2.31
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Family Functionality Among the Elderly With Chronic Illness

Abstract: The family APGAR scale was developed by Smilkstein, Ashworth, and Montano (1982). The satisfaction assessment of the elderly with chronic illness regarding family is essential. This study aims to describe the socio-demographic and clinical profile of elderly people with chronic illness and correlate with perceived family support. This is a cross-sectional, analytical study of 294 elderly people (51.4% female), patients at the Health Centre in the district of Viseu -Portugal, diagnosed with chronic illness (77.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 5 publications
0
13
1
4
Order By: Relevance
“…Despite its multiple chronic health problems, the study’s sample reported high family support. Family dysfunction was present at a quite lower proportion than in previous reports [5254]. This inconsistency may be due to the fact that in previous studies the age of the sample was limited to the geriatric population whereas in this study the age group was 18+ years old.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Despite its multiple chronic health problems, the study’s sample reported high family support. Family dysfunction was present at a quite lower proportion than in previous reports [5254]. This inconsistency may be due to the fact that in previous studies the age of the sample was limited to the geriatric population whereas in this study the age group was 18+ years old.…”
Section: Discussioncontrasting
confidence: 66%
“…Prior studies have noted the relationship between family APGAR scores and the presence of chronic illness [51, 52]. Despite its multiple chronic health problems, the study’s sample reported high family support.…”
Section: Discussionmentioning
confidence: 82%
“…ADHD is significant problems with attention and inhibitory control that cause attention deficits, hyperactivity, or impulsiveness with academic difficulties as are problems in relationship with family members [3]. TS/KS, a chromosome structure is altered and govern physical and medical characteristics, such as susceptibility to lymphedema, osteoporosis and fractures, structural malformations of the kidney, autoimmune thyroiditis, diabetes mellitus, inflammatory bowel disease [4][5][6], or higher risks for scoliosis, lordosis, and kyphosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerable situations have been found to exhibit relatively enduring health behavior, health values, family support, and health risk perceptions of families that can be developed and performed [7,8]; and situations of disability/worse health problem can compromise the independence and functional capacity of the vulnerable children thus making them dependent on caregivers, and inducing functional impairment in family, social, and academic settings that was similar in these groups of children and caused problems regarding families' health issues and general dysfunctional family support [9][10][11][12][13]. These untreated health problems may lead to major complications or complex limitations in activity and participation family time [3,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical evidence to guide health professional collaborate with families to provide family health promotion intervention. Especially, disturbances in family function were related to a high risk of family depression [7,9,13].…”
Section: Introductionmentioning
confidence: 99%